2017
DOI: 10.1128/iai.00406-17
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resistance to Intradermal Francisella tularensis LVS Infection by Inactivation of the Sts Phosphatases

Abstract: The uppressor ofCR ignaling proteins (Sts-1 and Sts-2) are two homologous phosphatases that negatively regulate signaling pathways in a number of hematopoietic lineages, including T lymphocytes. Mice lacking Sts expression are characterized by enhanced T cell responses. Additionally, a recent study demonstrated that mice are profoundly resistant to systemic infection by , with resistance characterized by enhanced survival, more rapid fungal clearance in key peripheral organs, and an altered inflammatory respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…4D) at 48 h postinfection. Mice infected with F. novicida by MNA intradermal delivery presented a typical splenic cellular response consistent with tularemia; the infiltration of monocytes and neutrophils without the expansion of T cells led to a relative percentage shift similar to that expected with other Francisella infection models and routes (35)(36)(37).…”
Section: Resultssupporting
confidence: 62%
“…4D) at 48 h postinfection. Mice infected with F. novicida by MNA intradermal delivery presented a typical splenic cellular response consistent with tularemia; the infiltration of monocytes and neutrophils without the expansion of T cells led to a relative percentage shift similar to that expected with other Francisella infection models and routes (35)(36)(37).…”
Section: Resultssupporting
confidence: 62%
“…The lessons learned from studies with mice that are resistant to C. albicans will likely have significance for optimizing the immune response to other pathogens. In this regard it is interesting that Sts − / − mice are also resistant to infection by the bacterial pathogen Franciscella tularensis (Parashar et al, 2017 ). Finding new ways to selectively boost immune function will be particularly important for types of infections that are characterized by excessive inflammatory damage.…”
Section: Discussionmentioning
confidence: 99%
“…Analogous to the heightened activation seen in T cells lacking Sts expression, one likely scenario is that innate immune cells lacking Sts expression respond to microbial challenge more actively and effectively, allowing them to overcome infection more readily. Support for this model comes from the recent observation that Sts − / − monocytes restrict the intracellular-replicating bacterial pathogen Francisella tularensis LVS with 10-fold greater efficiency than wild type monocytes, thereby enhancing host survival following a lethal infectious dose (Parashar et al, 2017 ). It remains to be determined whether the same mechanism responsible for enhanced Francisella clearance is also responsible for optimal fungal clearance during C. albicans systemic infection.…”
Section: Mutant Mice That Display Resistance To C Albicansmentioning
confidence: 99%
“…BMMs that are mobilized in response to bacterial infections within peripheral tissues are known to be potent inducers of pro-inflammatory interferons (eg, IFNγ), as well as additional cytokines and chemokines such as IL-1, IL-18, Ccl3, Cxcl9, and others. 32,33 Because monocytes lacking Sts expression display increased bactericidal activity toward internalized F. tularensis LVS ex vivo, 29 we examined whether cytokine production was deregulated. We infected wild type and Sts −/− BMMs ex vivo with LVS, and evaluated supernatant cytokine levels 24 hours postinfection.…”
Section: Increased Ifnγ Produced By F Tularensis Lvs-infected Sts mentioning
confidence: 99%
“…3.2 | Role of IFNγ in potentiating responses of BMMs to intracellular F. tularensis LVSPreviously, we demonstrated that Sts −/− BMMs restrict intracellular F. tularensis LVS with greater efficiency than wild type cells 29. To investigate a functional role for IFNγ during ex vivo monocyte responses, we cultured infected monocytes in the presence of exogenous IFNγ.…”
mentioning
confidence: 99%